Incidental diagnosis of a large aortopulmonary window with reversible pulmonary arterial hypertension in adult age and its surgical management. Issue 6 (19th April 2020) - Khanna, Sudhansoo; Mahajan, Sachin; Halder, Vikram; Gowda, Nischitha
Abstract: Aortopulmonary window (APW) is a rare congenital cardiac condition. A large number of patients with a large APW usually die within 1 year of age. It is extremely rare to find cases of APW surviving till adult age and it is still rare to surgically treat such patients who are incidentally detected in adult age because such subsets of patients invariably have associated pulmonary vascular obstructive disease in advanced stage and thus there is therapeutic dilemma to surgically correct these patients. Although cases of uncorrected AP window presenting in adulthood have been reported but literature on surgically treated AP window in adult populations is limited. We describe case of APW in a 26‐year‐old male patient who was diagnosed incidentally while suspecting infective endocarditis and was subsequently surgically closed successfully with polytetrafluoroethylene patch after confirming reversibility of pulmonary arterial hypertension which is the key for successful outcome.